A revision of the Indian species of Oligosita Walker (Hymenoptera: Trichogrammatidae) - Begum, Salma; Anis, Shoeba Binte; Khan, Mohd Talib (Zootaxa, 2015)
The Indian species of the genus Oligosita Walker, 1851 (Hymenoptera: Trichogrammatidae) are revised. One new species, Oligosita aseta Begum & Anis, sp. nov., is described based on specimens collected from Kerala, India. A key to the 16 Indian species of the genus is also given.